Cystatin C and creatinine eGFR reference intervals in healthy adults from Cameroon - Kågedal, Bertil; Dernroth, Dženeta Nezirević; Edinga-Melenge, Bertille Elodie; Tchapmi, Adrienne Yakam; Nansseu, Jobert Richie; Ama Moor, Vicky Jocelyne; Belinga, Suzanne; Hanberger, Håkan; Helldén, Anders (SCANDINAVIAN JOURNAL OF CLINICAL & LABORATORY INVESTIGATION, 2025)
Several equations are available for estimation of glomerular filtration rates (eGFRs) from serum cystatin C and creatinine, but data on reference intervals from healthy subjects are scarce. Employing nine well-known equations, we calculated eGFRs for healthy Cameroonians, 194 men and 187 women 18-71 years of age. Reference intervals were calculated using conventional techniques. For subjects < 50 years of age the eGFR reference intervals were with CAPA (men; women) 70.1-127.1; 79.9-172.2, with CKD-EPI 75.1-131.2; 81.3-135.5, with LM rev 65.4-106.5; 61.4-110.3, with CKD-EPI 74.1-127.2; 67.0-129.8, with mean (LM rev, CAPA) 72.2-110.6; 72.8-136.9, with CKD-EPI 81.1-126.6; 77.0-135.7, with EKFC 85.5-116.3; 83.3-124.8, with EKFC 69.4-114.2; 62.8-114.3, and with EKFC 82.5-114.0: 77.1-116.4 mL/min/1.73 m , respectively. Median eGFR was significantly higher than eGFR irrespective of equations used. The eGFR difference between healthy men and women aged < 50 years may be explained by lower production rates of cystatin C in women. The higher eGFR reference intervals compared to that of eGFR may be caused by increased tubular secretion of creatinine or increased production of cystatin C in the cohorts used for establishing the equations relative the case in healthy subjects. This suggests that the eGFR equations need to be further assessed regarding accuracy to adequately correspond to true GFR.